Menakar Prinsip-Prinsip Filosofis dalam Pembelajaran Raudlatul Athfal (THUFULA, 2013)
Analysis of learning development at the level of Raudlatul Athfal (RA) gives the feel of a dialogical existence as a base for Islamic education reunited with the latest educational globalized reality. Learning patterns that will be applied at RA level are necessarily exposed to the offred curriculum systematization. Would it offer a foothold to the scienctific dichotomy or integrating aspects? Both of these realities became the basis for explaining the essential scientific development in RA level. Philosophical principles in RA learning development definitely should be able to do a reading to the early growth dynamics of thought in education. The existence of Islamic educational thought as the learning basis in the RA’s development is essentially related to Greek thought underlying earlier. The intersection of thisthought should undoubtedly be realized so that the achievement of the learningphilosophical principles is globally recognized.